TOWARDS EUROPEAN PRIVATE LAW (EUROPEANIZATION OF PRIVATE LAW) - Simonović, Ivana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The concept of European Private Law can be approached from different perspectives. One approach explaines European Private Law as European ius commune, based on different national private law systems of Europe which together represent a common legal tradition. In the literature this concept is known as acquis commun. A fundamentally divergent approach primarily focuses on the European Union’s positive law – directives and regulations, that regulate relations between private parties. This acqius communautaire is fragmentary in nature and consists of intelectually unconected rules on highly specific matters of law. Neither of these two approaches provide complete picture of European Private Law. Therefore, it will be necessary to intelectually integrate them into one unified legal system able to show variety of different legal sources. Besides acqius communautaire, there are model-rules based on common legal tradition of european countries, meant to overarch different national systems and become a reference texts for the future discussion on europeanizing private law.
Keywords: European private law; Private law of European Union; Europeanization of private law; European Civil Code